Theoretical foundations of Islamic banking and its current place in the world economy - S. A. Pshibieva (Путеводитель предпринимателя, 2021)
The research is aimed at studying the basic principles of Islamic banking and its modern distribution. This paper analyzed the development of Islamic banking in the world: in the Arab countries, Europe, the CIS countries and Russia.